ANALISA HUBUNGAN STATUS GIZI DAN RIWAYAT PENYAKIT DENGAN KELELAHAN KERJA DI PT X - IZZA AMALIA (UNUSA Press, 2019)
Fatigue can lead to a decrease in productivity and increase the incidence of workplace accidents. The purpose of this study was to analyze the relationship between nutritional status and history of disease with work fatigue in workers at PT. X. This study was an observational study using a cross-sectional approach. The sample of this study was the total population of 45 workers from the morning shift workers. The independent variables of this study were nutritional status and disease history. The dependent variable was work fatigue. Coefficient correlation is used as data analysis to determine the strength of the relationship of the variables. The results showed that some workers’ nutritional status was fat (57.8%), and as much as (26.7%) workers had history of a certain disease. The conclusion of this study is both nutritional status and history of disease have a moderate relationship with work fatigue in workers of morning shift at PT.X. A monitoring of nutritional status from the companies is needed to be done for the workers also regularly holding a physical activity or exercise every once a week and conducting regular health checks can be done to maintain the good condition of the workers. Keywords : Fatigue, Nutritional Status, Medical of Disease